Livestock feed and forage management and utilization innovations - Mekonnen, Kindu; Bezabih, Melkamu; Adie, Aberra; Gebreyes, Million; Thorne, Peter J.; Seifu, Haimanot (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Presentation in Addis Ababa, Ethiopia March 27-28, 2023. Livestock feed and forage management and utilization innovations